First Victims at Last: Disability and Memorial Culture in Holocaust Studies - Zwick, Tamara (Conatus - Journal of Philosophy, 2019)
This essay begins with a Berlin memorial to the victims of National Socialist “euthanasia” killings first unveiled in 2014. The open-air structure was the fourth such major public memorial in the German capital, having followed earlier memorials already established for Jewish victims of Nazi atrocity in 2005, German victims of homosexual persecution in 2008, and Sinti and Roma victims in 2012. Planning for the systematic persecution and extermination of at least 300,000 infants, adolescents, and adults deemed “life unworthy of life” (Lebensunwertes Leben) long preceded and extended beyond the 12-year Nazi period of massacre linked to other victim groups. Yet those constructing collective memory projects in Berlin appear to consider these particular victims as an afterthought, secondary to the other groups. Rather than address the commemorations themselves, this essay addresses the sequence in which they have appeared in order to demonstrate a pattern of first-victimized/last-recognized. I argue that the massacre of Jews, Roma, homosexuals, and others had to come into legal jurisprudence, scholarship, and public memory projects first before the murdered disabled body and its related memorialization could be legitimized as a category of violence important in and of itself. I argue further that the delay is rooted in a shared trans-Atlantic history that has failed to interrogate disability in terms of the social and cultural values that categorize and stigmatize it. Instead, the disabled body has been seen as both a physical embodiment of incapacity and a monolith that defies historicization. An examination of the broader foundation behind delayed study and representation that recognizes the intersection of racism and ableism allows us to reconfigure our analysis of violence and provides fertile ground from which to make connections to contemporary iterations still playing out in the present.